Актуальні проблеми національно-патріотичного виховання майбутніх правоохоронців - Ряшко, В. І.; Ряшко, В. И.; Rjashko, V. (My University, 2010)
The article deals with the actual problem of national and patriotic treatment of cadets of students in the higher educational establishments. Also it reveals the role and the place of the leading staff, professors and teachers, in planning and organization of educational-treating process directed on forming of the inner world, national and patriotic consciousness of the future law enforcement workers of Ukraine.
Ряшко В. І. Актуальні проблеми національно-патріотичного виховання майбутніх правоохоронців / В. І. Ряшко // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 341-350.
Keywords: національно-патріотичне виховання майбутніх правоохоронців; формування духовності, національно-патріотичної свідомості майбутніх робітників правоохоронних органів України; национально-патриотическое воспитание будущих правоохранителей; формирование духовности, национально-патриотического сознания будущих работников правоохранительных органов; national-patriotic education of the future of law enforcement officers; the formation of spiritual, national and patriotic consciousness of future law enforcement